Synthesis of Phosphonates, Phosphinates and Tertiary Phosphine Oxides by Pd- or Ni-Catalyzed Microwave-Assisted P–C Coupling Reactions without the Addition of Conventional Ligands - Henyecz, Réka; Keglevich, György (Current Organic Chemistry, 2021)
Microwave (MW)-assistance may be a powerful tool in the Hirao P–C coupling reactions of vinyl/aryl halides with dialkyl phosphites in the presence of Pd-catalysts/Pligands elaborated forty years ago. This review surveys the development of this reaction by showing the expansion of the reagents and catalysts, as well as the information accumulated. The stress was laid on the “green” aspects, the simplification of the catalyst systems, and the reliable mechanistic details in order to be able to establish the optimum conditions. The best protocol involves the use of some excess of the >P(O)H reagent to ensure the PdII→Pd0 reduction and, via its trivalent tautomeric form (>POH), also the P-ligand. The overall rate is the result of two factors, the activity of the catalyst complex formed, and the reactivity of the reactants in the P–C coupling reactions. The nature of the aryl substituents in Ar2P(O)H influences both components. NiII salts may also be used as the catalyst precursor, however, despite the PdII→Pd0→PdII route, in this case, a NiII→NiIV→NiII sequence was proved.
Keywords: phosphine oxides